THE ROLE OF PRODUCTIVE ZAKAT IN TAPIN REGENCY ON THE ECONOMIC EMPOWERMENT OF MSMES: CONTRIBUTIONS AND PROBLEMS - Sauqi, Muhammad; Rusdiana, Rusdiana; Dairobi, Dairobi (AL-QARDH, 2024)
The purpose of this research is the contribution, the problem of productive zakat funds to the economic empowerment of MSMEs. This study uses a type of field research or it can be called (file research). The approach in this study uses a qualitative approach that is descriptive. The data sources used are primary and secondary data sources. Data collection techniques use observation, interviews, and documentation. Data analysis methods through data reduction, data presentation, and conclusions. The results obtained from the research are: first, in the productive zakat contribution activities carried out by BAZNAS Tapin there are two mechanisms, namely proposals and territorial programs. The pattern of zakat contribution to BAZNAS Tapin uses an even pattern, which is given to all groups, in accordance with Islamic law. But BAZNAS Tapin in contributing productive zakat prioritizes groups that are still able to be empowered (productive age/willing to try). Second, in general, the problems faced by BAZNAS Tapin in carrying out productive zakat contribution activities can be seen from the four management functions of productive zakat management planning, mustahik requests that are not in line with the skills they have. Organizing, in the mustahik election of BAZNAS Tapin, did not go directly into the field but collaborated with the sub-district UPZ and the Village UPZ. Briefing, there is no technical assistance. Supervision, Baznas cannot routinely supervise mustahik developments once a month. Third, the solutions provided by BAZNAS Tapin to all the problems experienced, namely: improving the performance of Amil, socialization, and cooperating with the District UPZ and Village UPZ